Antibiotics Contaminated Irrigation Water: An Overview on Its Impact on Edible Crops and Visible Light Active Titania as Potential Photocatalysts for Irrigation Water Treatment - Jalloul, Ghadeer; Keniar, Imad; Tehrani, Ali; Boyadjian, Cassia (Frontiers in Environmental Science, 2021)
Sub-therapeutic levels of antibiotics (ABs) are given to animals and poultry to promote growth and reduce disease. In agricultural environments, ABs reach croplands via animal manure used as fertilizer and/or the use of AB-contaminated irrigation water. The heavy use and the continuous discharge of ABs into the ecosystem raise growing concerns on the ABs contamination of edible crops, which affects the food chain and imposes risks to human health. Tetracyclines (TCs) are among the most widely used ABs, and they are detected in measurable concentrations in soil and water around the world. This review discusses TCs contamination of irrigation water, its impact on edible crops, and the potential risks of crop contamination with ABs to human health. We summarize the literature on tetracyclines presence in water environments, and propose solar-mediated photocatalytic degradation as a promising method to remove tetracyclines from irrigation water. Titania (TiO2) semiconductor is often used as an efficient and low-cost photocatalyst for this process. However, the photocatalytic activity of TiO2 is limited to the UV region of the light spectrum (200–400 nm), and modifications are required to expand its activity to the visible light region. We provide holistic guidance on developing a visible light–active TiO2-based photocatalyst to remove tetracyclines and other ABs from water. We also provide a detailed summary of recent advances to expand the light range of TiO2 activity from the UV region to the visible light region. Finally, we highlight the best TiO2 systems for eco-friendly, cost effective, and visible light–activated photocatalytic degradation of ABs in water.